Reflections throughout the COVID-19 Lockdown: What Do I Need for Successful Learning of Engineering? - Víctor Revilla-Cuesta (MDPI AG, 2021)
The intention of this study was to identify the elements that engineering students consider fundamental for successful learning on engineering courses. The aim was to provide generic guidelines suitable for any engineering course with which the teaching may be adapted in the light of comments from students, while student learning improves. The abrupt transition from face-to-face to asynchronous online teaching due to the COVID-19 pandemic prompted reflection among students on both teaching methods. Students were invited to evaluate each method through a survey of open-ended questions, identifying useful elements for their learning. The survey was repeated over nine weeks, to obtain the views of students after they had accepted the change and had critically analyzed how to improve online teaching. A cross-coded qualitative and mixed (word counting) analysis showed that the explanation of engineering concepts should be organized, hierarchical, repetitive, and exemplified. Furthermore, the teacher should link all the activities and projects to the concepts explained and quickly solve any doubts that they raised. As a consequence of the online teaching resulting from COVID-19, the need of independent student learning and peer support was also very evident. Teaching functions are essential on engineering courses, as teachers have to explain the overall concepts carefully, identify the key concepts, and demonstrate their industrial and professional applications. Furthermore, teaching methodologies that balance these aspects with autonomy and peer support for learning on engineering courses should be promoted.